Simulated Pediatric Respiratory Workshop - Amanda Rogers; Jennifer Di Rocco; Paula Soung (Association of American Medical Colleges, 2014)
Abstract Introduction This workshop addresses the most common causes of pediatric respiratory distress and failure, including asthma, complicated pneumonia, bronchiolitis, and upper-airway obstruction. It is geared at medical students and pediatric residents. The goal is to teach them how to manage pediatric respiratory distress and failure in a safe, controlled environment and receive feedback on their clinical skills. Methods The workshop consists of three hands-on, case-based scenarios for participants to rotate through. A pre- and posttest evaluation was created for participants to complete, which assesses their clinical knowledge and clinical confidence. A performance-based checklist was created for observers to complete which assesses the participants' clinical performance. Results Participating residents were found to have statistically significant improvements in their clinical knowledge, confidence, and performance managing pediatric respiratory distress and failure following the workshop. This improvement was found to be sustained even 6 months after the workshop. Discussion This workshop successfully teaches learners how to manage pediatric respiratory distress and failure with a comprehensive assessment of clinical knowledge, clinical confidence, and clinical performance.